SURVEI PH SALIVA PADA ANAK RETARDASI MENTAL DI SLB KABUPATEN JEPARA TAHUN 2016 - Erni Mardiati; Irma H.Y Siregar; Tika Dui Dara Ayuningtiyas (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2016)
TITLEThe survey of pH saliva in mental retardation children of SLB Kabupaten Jepara in 2016ABSTRACTMental retardation is a retardation abnormality intellectual functioning and adaptive capabilities significantly with the signs shown before the age of 18 years. People with mental retardation have oral health and hygiene were worse compared with normal children. Purpose of this study was to determine the state of buffer of saliva in mentally retarded children in SLB Jepara.This research is a survey and cross sectional study as research design, and sampling using stratifiedrandom sampling. This type is used by researcher to know some of the variables in the population, because the total number of students in SLB Jepara was 225 and researchers get 20% of the total number of students is 45, and are grouped into 15 people with mild mental retardation, 15 people with moderate mental retardation and 15 with severe mental retardation.pH saliva of mentally retarded children tend to be more acidic, is caused by the exclusion or secretion of buffer saliva is less than the maximum because of the work of the autonomic nervous activity which includes the sympathetic and parasympathetic nervous. The results showed that the average pH of saliva in children with mental retardation in Jepara regency highest in SLB show in an acidic state by 67% and the lowest is in the alkaline state in the amount of 13%. Parents need to pay more attention to hygiene and dental health of children, and also train children to always keep his own personal hygiene, especially in terms of oral health, it could also teach brushing teeth early. And the researchers suggested that the school makes an effort dental health program in schools with programs that can be applied to children with mental retardation, such as brushing their teeth together or perform routine checks every 6 months. Keywords : Mental retardation, pH Saliva